Electrochemical Capacitors Based on Aligned Carbon Nanotubes Directly Synthesized on Tantalum Substrates - Kim, Byungwoo; Chung, Haegeun; Min, Byoung Koun; Kim, Honggon; Kim, Woong (WILEY-V C H VERLAG GMBH, 2010)
We demonstrate that vertically aligned carbon nanotubes can be synthesized directly on tantalum substrate via water-assisted chemical vapor deposition and evaluate their properties as electrochemical capacitors. The mean diameter of the carbon nanotubes was 7.1 +/- 1.5 nm, and 70% of them had double walls. The intensity ratio of G-band to D-band in Raman spectra was as high as 5, indicating good quality of the carbon nanotubes. Owing to the alignment and low equivalent series resistance, the carbon nanotube based supercapacitors showed good rate performance. Rectangular shape of cyclic voltammogram was maintained even at the scan rate of > 1 V/s in 1 M sulfuric acid aqueous solution. Specific capacitance was well-retained (similar to 94%) even when the discharging current density dramatically increased up to 145 A/g. Consequently, specific power as high as 60 kW/kg was obtained from as-grown carbon nanotubes in aqueous solution. Maximum specific energy of similar to 20 Wh/kg was obtained when carbon nanotubes were electrochemically oxidized and operated in organic solution. Demonstration of direct synthesis of carbon nanotubes on tantalum current collectors and their applications as supercapacitors could be an invaluable basis for fabrication of high performance carbon nanotube supercapacitors
Keywords: DIRECT GROWTH; SUPERCAPACITORS; ELECTRODE; FOILS